2007
DOI: 10.1016/j.jchromb.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of trans-resveratrol and detection of its metabolites in human plasma and urine by high performance liquid chromatography

Abstract: We describe a reversed-phase HPLC method that uses gradient elution and UV detection (325 nm) to determine levels of resveratrol and identify 6 major conjugated metabolites in the plasma and urine of human volunteers after administration of a single oral dose of 1 g. Waters Atlantis C 18 3μ served as the stationary phase. The gradient was formed using ammonium acetate and methanol, containing 2% propan-2-ol. Detection is linear between 5 ng/mL and 500 ng/mL in plasma (5-1000 ng/mL in urine). The coefficient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 25 publications
2
137
1
Order By: Relevance
“…Resveratrol and its metabolites were extracted and separated using a gradient UV-high-performance liquid chromatography system (Waters Breeze) as described before (29). Separation was achieved on a Waters Atlantis C18 column (4.6 Â 150 mm, 3 Am; Waters) in combination with a Waters Atlantic C18 guard column (4.6 Â 20 mm, 5 Am).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol and its metabolites were extracted and separated using a gradient UV-high-performance liquid chromatography system (Waters Breeze) as described before (29). Separation was achieved on a Waters Atlantis C18 column (4.6 Â 150 mm, 3 Am; Waters) in combination with a Waters Atlantic C18 guard column (4.6 Â 20 mm, 5 Am).…”
Section: Methodsmentioning
confidence: 99%
“…The retention time of resveratrol was 18.6 min; its lower limit of detection was 5 ng/mL. This method has been validated for resveratrol in terms of interday and intraday variability, recovery, accuracy, and precision (29). As resveratrol metabolites were not available in sufficient quantities for method development, their quantities were calculated based on the assumption that recovery characteristics and relationship between peak area ratios and concentrations were the same as those for resveratrol.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, no toxic effects were observed in rats given a supplementation of 300 mg resveratrol/day for 4 weeks. In humans, Boocock et al found no toxicity after administration of a single dose of up to 5 g resveratrol (Boocock et al, 2007). In addition, clinical, biochemical, and hematological indices revealed no serious toxic effects in 44 healthy volunteers (10-12 per group) administered resveratrol for 29 days at a daily dose of 0.5, 1.0, 2.5, or 5.0 g. (Brown et al, 2010).…”
Section: Toxicity Of Resveratrolmentioning
confidence: 99%
“…The amount of resveratrol ingested from dietary sources, such as red wine and juices, rarely exceeds 5 mg/L and often results in plasma levels that are either not detectable or several orders of magnitude below the micromolar concentrations that are employed in experimentation in vitro, i.e., $32 nM to 100 lM (Smoliga et al, 2011). For example, administration of about 25 mg resveratrol resulted in plasma concentrations of the free form that ranged from 1 to 5 ng/mL , and administration of higher doses (up to 5 g) increased the plasma resveratrol concentration to about 500 ng/mL (Boocock et al, 2007). The low doses of resveratrol observed in the plasma after ingestion are very low, as the concentrations used in vitro are not reached.…”
Section: Bioavailability Of Resveratrol and Plasma Levelsmentioning
confidence: 99%
“…Although several reports have described the pharmacokinetics of resveratrol in animal model systems (reviewed in Table 2 summarizes the widely varying circumstances under which resveratrol, as a pure compound or in wine and/or other beverages, has been investigated in human subjects (64)(65)(66)(67)(68)(69)(70)(71). It is clear from the tabular clinical observations that resveratrol is rapidly absorbed following oral administration; levels are detectable in both plasma and urine, with the maximum plasma concentrations being reached between 30 and 60 min after administration.…”
Section: Clinical Studiesmentioning
confidence: 99%